Positive electrode active material, method of preparing positive electrode active material, and rechargeable lithium battery including positive electrode active material

CN122992016APending Publication Date: 2026-10-27SAMSUNG SDI CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610535023.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2026-03-19
Filing Date
2026-04-22
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

该包覆工艺可通过湿式工艺(湿法)(即,使用溶剂)或通过干式工艺(干法)(即,不使用溶剂)进行,但是严重依赖于湿式工艺增加正电极活性物质的制造成本

Benefits of technology

[0024]根据一些实施方式的制备正电极活性物质的方法可提供具有均匀的包覆、改善的导电性和降低的制造成本的正电极活性物质。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122992016A_ABST
    Figure CN122992016A_ABST
Patent Text Reader

Abstract

The present invention relates to a positive electrode active material, a method of preparing a positive electrode active material, and a rechargeable lithium battery including the positive electrode active material. The positive electrode active material according to some embodiments of the present disclosure can include: core particles including a lithium transition metal composite compound, and a coating layer. The coating layer can be disposed on a surface of the core particles. The coating layer can include graphene that can have a layered structure. The positive electrode active material can have a powder conductivity greater than or equal to about 0.1 mScm ‑1 when measured at a pressure of 250 MPa.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This disclosure relates to positive electrode active materials, methods for preparing positive electrode active materials, and rechargeable lithium batteries including positive electrode active materials. Background Technology

[0002] Portable information devices (such as cellular phones, laptops, or smartphones) and electric vehicles already use rechargeable lithium batteries with high energy density as their power source. Recently, research has been actively underway to use rechargeable lithium batteries with high energy density as a power source for hybrid or electric vehicles, or as a power storage source.

[0003] In the manufacture of electrode plates, to improve the conductivity of the electrode (whose main component is a non-conductive positive electrode active material), research is actively underway on techniques for coating the positive electrode active material with conductive materials exhibiting conductive properties, such as carbon materials and conductive polymers. This coating process can be carried out via a wet process (i.e., using a solvent) or a dry process (i.e., without using a solvent), but the heavy reliance on wet processes increases the manufacturing cost of the positive electrode active material.

[0004] Therefore, it is advantageous to develop positive electrode active materials that enable uniform coating, improved conductivity, and reduced manufacturing costs. Summary of the Invention

[0005] The invention provides a positive electrode active material, a method for preparing the positive electrode active material, and a rechargeable lithium battery including the positive electrode active material. The positive electrode active material includes (or the method for preparing the positive electrode active material enables) a uniform coating, and the positive electrode active material includes improved conductivity (or the method for preparing the positive electrode active material improves the conductivity of the positive electrode active material), while allowing for reduced manufacturing costs. This is due to a coating layer, including graphite particles, formed on the surface of the core particles on the positive electrode active material, which is achieved through dry mixing (dry blending).

[0006] Positive electrode active materials according to some embodiments of this disclosure may include: core particles comprising a lithium transition metal complex compound and a coating layer. The coating layer may be disposed on the surface of the core particles. The coating layer may include graphene having a layered structure. When measured at a pressure of 250 MPa, the positive electrode active material may have a density greater than or equal to about 0.1 mS / cm. -1 The electrical conductivity of the powder.

[0007] In some embodiments, the lithium transition metal complex compound may include lithium cobalt-based oxides represented by:

[0008] Li a2Co x2 M 3 y2 O 2-b2 X b2 .

[0009] 0.9 ≤ a² ≤ 1.8, 0.7 ≤ x² ≤ 1, 0 ≤ y² ≤ 0.3, 0.9 ≤ x² + y² ≤ 1.1, and 0 ≤ b² ≤ 0.1. M 3 X can be Al, B, Ba, Ca, Ce, Cr, Cu, Fe, Mg, Mn, Mo, Ni, Se, Si, Sn, Sr, Ti, V, W, Y, Zn, Zr, or combinations thereof. X can be F, P, S, or combinations thereof.

[0010] In some implementations, the core particle may be in the form of a single particle.

[0011] In some embodiments, the core particles may include an average particle size D greater than or equal to about 0.1 μm and less than about 9 μm. 50 Small particles and an average particle size D of approximately 9 μm to approximately 30 μm 50 Large particles.

[0012] In some embodiments, the coating layer may include graphene having 2 to 50 layers.

[0013] In some implementations, the interlayer spacing d of the layered structure 002 It can be approximately 0.320 nm to approximately 0.350 nm.

[0014] In some embodiments, graphene may have a strength of about 0.15 to about 0.50, expressed as a Raman spectrum at 1350 cm⁻¹. -1 Nearby peak intensity I D At 1580 cm -1 Nearby peak intensity I G The ratio I D / I G .

[0015] In some embodiments, the graphene coating may be derived from graphite particles having an average size of less than or equal to about 2.5 μm.

[0016] In some embodiments, based on 100% by weight of the positive electrode active material, the positive electrode active material may include graphene in an amount from about 0.01% by weight to about 1% by weight.

[0017] In some embodiments, the coating layer may be a continuous film surrounding the surface of the core particle. The thickness of the coating layer may be from about 1 nm to about 40 nm.

[0018] A method for preparing a positive electrode active material according to some embodiments of this disclosure may include: preparing core particles comprising a lithium transition metal composite compound; preparing an average size D of less than or equal to about 2.5 μm. 50 Graphite microparticles; and dry mixing of core particles and graphite microparticles to obtain a positive electrode active material.

[0019] In some embodiments, preparing graphite particles may include pulverizing them to have an average size D of about 3 μm to about 25 μm. 50 Flake-like (scaly) graphite.

[0020] In some embodiments, pulverizing flake graphite can be performed using a ball mill apparatus comprising zirconia beads, each having a size of about 1 mm to about 3 mm. Pulverizing the flake graphite can be performed at speeds ranging from about 200 rpm to about 5,000 rpm for a time period ranging from about 30 minutes to about 4 hours.

[0021] In some embodiments, the dry mixing of core particles and graphite microparticles can be carried out in amounts ranging from about 0.1 parts by weight to about 0.5 parts by weight per 100 parts by weight of core particles.

[0022] A rechargeable lithium battery according to some embodiments of this disclosure may include a positive electrode, a negative electrode, and an electrolyte. The positive electrode may include a positive electrode current collector and a positive electrode active material layer disposed on the positive electrode current collector, the positive electrode active material layer including the positive electrode active material as described above.

[0023] According to some embodiments, a coating layer including graphite microparticles can be formed on the surface of the core particles of the positive electrode active material, thereby achieving uniform coating of the positive electrode active material, improving conductivity, and reducing manufacturing costs. Furthermore, because the rechargeable lithium battery includes conductive positive electrode active material, the amount of conductive material can be minimized during the manufacturing of the positive electrode, thereby allowing for batteries with high capacity and high energy density.

[0024] The method for preparing positive electrode active material according to some embodiments can provide positive electrode active material with uniform coating, improved conductivity and reduced manufacturing cost. Attached Figure Description

[0025] Figures 1 to 4 The diagrams illustrate, for example, some embodiments of rechargeable lithium batteries according to this disclosure.

[0026] Figure 5 These are scanning electron microscope images of the surface of the positive electrode active material prepared in Example 2 according to some embodiments of the present disclosure.

[0027] Figure 6 These are scanning electron microscope images of the surface of the positive electrode active material prepared in Comparative Example 1 according to some embodiments of the present disclosure.

[0028] Figure 7 These are scanning electron microscope images of the surface of the positive electrode active material prepared in Comparative Example 5 according to some embodiments of the present disclosure.

[0029] Figure 8 This is a transmission electron microscope image of the coating layer in the cross section of the positive electrode active material prepared in Example 1 according to some embodiments of the present disclosure.

[0030] Figure 9 This is a transmission electron microscope image of the coating layer in the cross section of the positive electrode active material prepared in Example 2 according to some embodiments of the present disclosure.

[0031] Figure 10 This is a graph showing the powder resistance versus pressure of the positive electrode active material prepared in Examples 1 to 3 according to some embodiments of the present disclosure. Detailed Implementation

[0032] Specific implementation methods will be described in detail below so that those skilled in the art can readily implement them. However, this disclosure may be implemented in many different forms and is not to be construed as limited to the implementation methods set forth herein.

[0033] The terminology used herein is for describing some implementations and is not intended to limit the scope of this disclosure. Unless the context clearly specifies otherwise, singular expressions include plural expressions.

[0034] As used herein, “combinations thereof” means mixtures, laminates, complexes, copolymers, alloys, blends or reaction products of the constituent elements.

[0035] In this document, it should be understood that terms such as “comprising,” “including,” or “having” are intended to indicate the presence of the features, quantities, steps, elements, or combinations thereof embodied, but such terms do not preclude the possibility of the presence or addition of one or more other features, quantities, steps, elements, or combinations thereof.

[0036] In the accompanying drawings, for clarity, the thickness of layers, films, panels, or regions is exaggerated, and throughout the specification, the same reference numerals denote the same elements. It will be understood that when an element such as a layer, film, region, or substrate is referred to as being "on" another element, the element may be directly on said other element, or there may be intermediate elements present. In contrast, when an element is referred to as being "directly on" another element, there are no intermediate elements.

[0037] In this article, “layer” includes not only the geometry formed on the entire surface when viewed from a plan view, but also the geometry formed on a portion of the surface.

[0038] The average particle size can be measured using methods known to those skilled in the art (e.g., by a particle size analyzer or by transmission electron microscopy or scanning electron microscopy images). Alternatively, the average particle size value can be obtained by measuring using dynamic light scattering, performing data analysis, counting the number of particles in each particle size range, and calculating from the obtained value and / or measurement results. Unless otherwise defined, the average particle size D... 50 This can mean the diameter of particles that constitute 50% of the cumulative volume in the particle size distribution. In other words, unless otherwise defined, the average particle size D is... 50 This means the diameter of the particles representing 50% of the cumulative volume in the particle size distribution obtained by randomly measuring the size (diameter or major axis length) of approximately 20 particles in a scanning electron microscope image. In this paper, the size may vary depending on the particle shape relative to the object being measured. For example, the diameter may be measured for spherical particles, while the length of the major axis may be measured for non-spherical particles.

[0039] In this article, "or" is not interpreted as having an exclusive meaning; for example, "A or B" is interpreted as including A, B, and A+B.

[0040] The term "metal" is interpreted to include common metals, transition metals, and metalloids (semi-metals). As used herein, the term "metalloid" refers to an element that has properties intermediate between those of metals and nonmetals. Examples of metalloids include, but are not limited to, boron (B), silicon (Si), germanium (Ge), arsenic (As), antimony (Sb), and tellurium (Te).

[0041] Positive electrode active material

[0042] According to some embodiments, the positive electrode active material may include: a core particle comprising a lithium transition metal complex compound and a coating layer comprising layered graphene disposed on the surface of the core particle. When measured at a pressure of approximately 250 MPa, the positive electrode active material may have a strength greater than or equal to approximately 0.1 mS / cm. -1 The electrical conductivity of the powder.

[0043] The electrical conductivity of the positive electrode is crucial for improving the charge / discharge capacity, efficiency, and cycle life characteristics of rechargeable lithium-ion batteries. However, the lithium transition metal complex compounds that are the main components of the positive electrode are non-conductive materials and do not possess electrical conductivity themselves.

[0044] Manufacturing rechargeable lithium-ion batteries can include methods such as preparing a slurry by mixing a conductive material with a positive electrode active material, and using the slurry to manufacture the positive electrode. However, as the amount of conductive material added during the preparation of the positive electrode slurry increases to improve conductivity, the amount of positive electrode active material added relatively decreases, which limits the achievement of the desired energy density.

[0045] Another approach may involve coating the surface of the positive electrode active material with conductive carbon materials or conductive polymers. High capacity and high energy density can be achieved by reducing the amount of conductive material added during the preparation of the positive electrode slurry and increasing the amount of the added positive electrode active material, thereby overcoming the problems arising from mixing conductive materials during the preparation of the positive electrode slurry. There are two methods for coating the surface of the positive electrode active material with conductive materials: a wet method using solvents and a dry method without solvents. Uniform coating can be achieved primarily using the wet method. However, the increased manufacturing cost due to the necessity of using solvents is a problem, and if the manufacturing cost is reduced using the dry method, there is a problem: carbon materials typically have low dispersibility and therefore tend to agglomerate (coagulate), making uniform coating difficult.

[0046] Therefore, the inventors of this invention have designed a carbon material capable of ensuring high capacity and high energy density. This is achieved by reducing the amount of conductive material added and relatively increasing the amount of positive electrode active material added during the preparation of the positive electrode slurry. Furthermore, this is achieved by uniformly coating the surface of the positive electrode active material with conductive material (even if the coating process is dry coating) to reduce manufacturing costs. Therefore, the positive electrode active material coated with layered graphene can be uniformly coated even during dry coating, which reduces manufacturing costs, and since the positive electrode active material exhibits conductivity, high capacity and high energy density can be achieved by either not adding conductive material during the manufacture of the positive electrode or by minimizing the amount of conductive material during the manufacture of the positive electrode.

[0047] The powder conductivity of the positive electrode active material, measured at a pressure of 250 MPa, can be greater than or equal to approximately 0.2 mS / cm. -1 Greater than or equal to approximately 0.3 mScm -1 Greater than or equal to approximately 0.4 mScm -1 Greater than or equal to approximately 0.5 mScm -1 Or greater than or equal to approximately 0.6 mScm -1 There is no particular upper limit, because the higher the upper limit, the greater the powder conductivity, but it can be, for example, less than or equal to about 55 mS / cm. -1 Less than or equal to approximately 50 mScm -1 Less than or equal to approximately 45 mScm-1 Or less than or equal to approximately 42 mScm -1 The powder conductivity of the positive electrode active material can be measured as follows: For approximately 3g of the positive electrode active material, the powder resistance is measured using a powder resistance meter equipped with a 4-pin probe (e.g., PD-600, Nittoseiko Analytech) while controlling the pressure applied to the powder, and the reciprocal of the powder resistance value at a pressure of approximately 250 MPa is taken. Positive electrode active materials that meet the above powder conductivity exhibit powder conductivity, allowing for a minimization of the amount of conductive material added during the manufacture of the positive electrode, thereby enabling high capacity and high energy density.

[0048] Core Particles

[0049] The core particles include lithium transition metal complex compounds.

[0050] Lithium transition metal complexes can be used without limitation as positive electrode active materials for rechargeable lithium batteries. These lithium transition metal complexes can be compounds capable of lithium intercalation and deintercalation.

[0051] Lithium transition metal complex compounds may include lithium nickel-based oxides, lithium cobalt-based oxides, lithium manganese-based oxides, lithium iron phosphate (lithium iron phosphate)-based compounds, cobalt-free lithium nickel manganese-based oxides, lithium manganese-rich complex oxides, or combinations thereof.

[0052] The lithium transition metal complex of the core particles can be a compound represented by any of the following chemical formulas. Li a A 1-b X b O 2-c D c (0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.05); Li a Mn 2-b X b O 4-c D c (0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.05); Li a Ni 1-b-c Co b X c O 2-α D α (0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.5, 0<α<2); Li a Ni 1-b-c Mn b X c O 2-α D α(0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.5, 0<α<2); Li a Ni b CocL 1 d G e O2(0.90≤a≤1.8, 0≤b≤0.9, 0≤c≤0.5, 0≤d≤0.5, 0≤e≤0.1); Li a NiG b O2 (0.90≤a≤1.8, 0.001≤b≤0.1); Li a CoG b O2 (0.90≤a≤1.8, 0.001≤b≤0.1); Li a Mn 1-b G b O2 (0.90≤a≤1.8, 0.001≤b≤0.1); Li a Mn2G b O4 (0.90≤a≤1.8, 0.001≤b≤0.1); Li a Mn 1-g G g PO4 (0.90≤a≤1.8, 0≤g≤0.5); Li (3-f) Fe2(PO4)3 (0≤f≤2); and Li a FePO4 (0.90≤a≤1.8).

[0053] In the above chemical formula, A is Ni, Co, Mn, or a combination thereof; X is Al, Ni, Co, Mn, Cr, Fe, Mg, Sr, V, rare earth elements, or a combination thereof; D is O, F, S, P, or a combination thereof; G is Al, Cr, Mn, Fe, Mg, La, Ce, Sr, V, or a combination thereof; and L 1 It is Mn, Al, or a combination thereof.

[0054] The lithium transition metal complex compound of the core particle may include, for example, lithium nickel-based oxides represented by chemical formula 1, lithium cobalt-based oxides represented by chemical formula 2, lithium iron phosphate-based compounds represented by chemical formula 3 or 4, cobalt-free lithium nickel manganese-based oxides represented by chemical formula 5, or combinations thereof.

[0055] Chemical formula 1 is as follows:

[0056] [Chemical Formula 1]

[0057] Li a1 Ni x1 M 1 y1 M 2 z1 O2-b1 X b1 .

[0058] In chemical formula 1, 0.9 ≤ a1 ≤ 1.8, 0.3 ≤ x1 ≤ 1, 0 ≤ y1 ≤ 0.7, 0 ≤ z1 ≤ 0.7, 0.9 ≤ x1 + y1 + z1 ≤ 1.1, and 0 ≤ b1 ≤ 0.1. Furthermore, M... 1 and M 2 They are different elements, M 1 and M 2 Each of these elements independently is Al, B, Ba, Ca, Ce, Co, Cr, Cu, Fe, Mg, Mn, Mo, Nb, Si, Sn, Sr, Ti, V, W, Y, Zr, or combinations thereof. Furthermore, X is F, P, S, or combinations thereof.

[0059] In chemical formula 1, 0.6≤x1≤1, 0≤y1≤0.4, and 0≤z1≤0.4, or 0.8≤x1≤1, 0≤y1≤0.2, and 0≤z1≤0.2.

[0060] Chemical formula 2 is as follows:

[0061] [Chemical Formula 2]

[0062] Li a2 Co x2 M 3 y2 O 2-b2 X b2 .

[0063] In chemical formula 2, 0.9 ≤ a² ≤ 1.8, 0.7 ≤ x² ≤ 1, 0 ≤ y² ≤ 0.3, and 0.9 ≤ x² + y² ≤ 1.1. Furthermore, 0 ≤ b² ≤ 0.1, M 3 X is Al, B, Ba, Ca, Ce, Cr, Cu, Fe, Mg, Mn, Mo, Ni, Se, Si, Sn, Sr, Ti, V, W, Y, Zn, Zr, or combinations thereof. Furthermore, X is F, P, S, or combinations thereof.

[0064] Chemical formula 3 is as follows:

[0065] [Chemical Formula 3]

[0066] Li a3 Fe (1-x3) M 4 x3 PO4.

[0067] In chemical formula 3, 0.9 ≤ a³ ≤ 1.5, 0 ≤ x³ ≤ 0.4. Furthermore, M... 4is Al, B, Ca, Ce, Cr, Cu, La, Mg, Mn, Mo, Nb, Ni, Si, Sn, Sr, Ti, V, W, Y, Zn, Zr, or a combination thereof.

[0068] In Chemical Formula 3, 0.9≤a3≤1.5. For example, 0.9≤a3≤1.2 or 0.95≤a3≤1.1. In addition, 0≤x3≤0.4, 0≤x3≤0.3, 0≤x3≤0.2, 0≤x3≤0.1, or 0≤x3≤0.05.

[0069] Chemical Formula 4 is as follows:

[0070] [Chemical Formula 4]

[0071] Li a4 Mn x4 Fe (1-x4-y4) M 5 y4 PO4.

[0072] In Chemical Formula 4, 0.9≤a4≤1.5, 0.1≤x4≤0.9, 0≤y4≤0.9. Furthermore, M 5 is Al, B, Ca, Ce, Cr, Cu, La, Mg, Mo, Nb, Ni, Si, Sn, Sr, Ti, V, W, Y, Zn, Zr, or a combination thereof.

[0073] In Chemical Formula 4, 0.9≤a4≤1.5. For example, 0.9≤a4≤1.2, or 0.95≤a4≤1.1. In addition, 0.1≤x4≤0.9, 0.3≤x4≤0.9, or 0.4≤x4≤0.8, and 0≤y4≤0.4, 0≤y4≤0.3, 0≤y4≤0.2, 0≤y4≤0.1, or 0≤y4≤0.05.

[0074] Chemical Formula 5 is as follows:

[0075] [Chemical Formula 5]

[0076] Li a5 Ni x5 Mn y5 M 6 z5 O 2-b5 X b5 .

[0077] In Chemical Formula 5, 0.9≤a5≤1.8, 0.8≤x5<1, 0<y5≤0.2, 0≤z5≤0.2, 0.9≤x5+y5+z5≤1.1, and 0≤b5≤0.1. Furthermore, M 6X is Al, B, Ba, Ca, Ce, Cr, Fe, Mg, Mo, Nb, Si, Sn, Sr, Ti, V, W, Y, Zr, or combinations thereof. Furthermore, X is F, P, S, or combinations thereof.

[0078] Lithium transition metal complex compounds may include lithium cobalt-based oxides represented by Formula 2. When the core particles include lithium cobalt-based compounds, high-voltage designs for rechargeable lithium batteries are possible. Furthermore, the reliability and safety of rechargeable lithium batteries can be improved due to reduced gas generation at high voltages, and a synergistic effect can be achieved in fast-charging systems to suppress battery resistance.

[0079] Each core particle can be a secondary particle formed by the aggregation of multiple primary particles, or it can be a single particle. A single particle exists independently without grain boundaries, consists of a single particle, and can be a monolithic (monomer) structure, a unified structure, or a non-agglomerated particle, wherein the particles do not aggregate but exist as independent phases in terms of morphology, and can be represented as a single crystal. The geometry of the core particles is not particularly limited and can include various geometries such as polyhedra, spheres, ellipsoids, plates, rods, or irregular geometries. When the lithium transition metal complex includes a lithium cobalt-based oxide represented by Formula 2, the core particle can be in the form of a single particle.

[0080] The average particle size D of the core particles 50 The particle size can be from about 0.1 μm to about 30 μm, for example, from about 1 μm to about 25 μm, from about 1 μm to about 20 μm, from about 1 μm to about 18 μm, from about 3 μm to about 15 μm, or from about 5 μm to about 15 μm. Core particles with the above particle size range can achieve high capacity and high energy density. The average particle size can be obtained by selecting about 20 random particles from the scanning electron microscope image of the core particle, measuring their particle size (diameter, major axis, or major axis length), obtaining the particle size distribution, and then taking the size of the particles with a cumulative volume of 50% of the particle size distribution as the average particle size.

[0081] Core particles may have a bimodal form, including an average particle size D greater than or equal to about 0.1 μm and less than about 9 μm. 50 Small particles and an average particle size D of approximately 9 μm to approximately 30 μm 50Large particles. When the core particles are used in a mixed form of large and small particles (e.g., bimodal form), the small particles can fill the gaps between the large particles, thereby improving the integration density of the positive electrode active material per unit volume, and thus improving the energy density per unit volume of the positive electrode. The weight ratio of large to small particles included in the core particles is not particularly limited, but can be, for example, about 1:9 to about 9:1, about 2:8 to about 9:1, about 3:7 to about 9:1, about 4:6 to about 9:1, or about 5:5 to about 9:1.

[0082] Coating layer

[0083] The coating layer is disposed on the surface of the core particle and includes graphene with a layered structure. The positive electrode active material including the coating layer itself exhibits conductivity, which minimizes the amount of conductive material added during the manufacturing of the positive electrode and allows for a relatively larger amount of added positive electrode active material, thereby achieving high capacity and high energy density. Furthermore, the layered graphene structure allows for uniform coating even during dry coating, thereby reducing manufacturing costs.

[0084] The number of layers in the layered structure is not particularly limited, but can be represented, for example, as a layered structure of about 2 to about 50 atomic layers. The coating layer may include graphene with a layered structure of about 5 to about 50 layers, about 8 to about 49 layers, about 10 to about 48 layers, about 13 to about 47 layers, about 15 to about 46 layers, or about 17 to about 46 layers. The number of layers in the layered structure can be measured by high-resolution transmission electron microscopy (HR-TEM) images of the particles of the positive electrode active material.

[0085] The interlayer spacing d of the layered structure 002 The interlayer spacing d of the layered structure can be from about 0.320 nm to about 0.350 nm, for example, from about 0.325 nm to about 0.348 nm, from about 0.328 nm to about 0.345 nm, or from about 0.330 nm to about 0.342 nm. 002 When the above range is met, the conductivity of the positive electrode active material itself can be further improved. Interlayer spacing d 002 The interlayer spacing d of the layered structure can be measured using methods known to those skilled in the art. 002 The peaks on the 002 plane can be obtained through X-ray diffraction (XRD) of the coating layer, followed by analysis of these peaks. The 002 plane represents the range of approximately 25.0° < 2θ < 27.0°, where 2θ represents the diffraction angle of the incident rays. Standard procedures included in the XRD apparatus can be used for data processing and analysis, allowing the XRD measurement data to undergo noise removal (baseline setting), etc. Furthermore, the peak profiles on the 002 plane can be fitted using conventional fitting functions such as Gaussian or Lorentz functions. Additionally, the interlayer spacing d of the layered structure...002 The interlayer spacing d of graphite particles can be measured. 002 The method is used to measure the interlayer spacing d of the graphite particles. 002 It can be measured by XRD analysis of graphite particles.

[0086] The graphene coating may have a Raman spectral density of about 0.15 to about 0.50, for example about 0.15 to about 0.45, about 0.18 to about 0.45, or about 0.20 to about 0.40 at 1350 cm⁻¹. -1 Nearby peak intensity I D At 1580 cm -1 Nearby peak intensity I G The ratio I D / I G When graphene's I D / I G When the value meets the above range, the active material of the positive electrode can be endowed with its own powder conductivity.

[0087] The graphene coating can be derived from graphite microparticles. A coating layer of uniform thickness can be formed on the surface of the core particles, imparting conductivity to the positive electrode active material powder. "Graphite microparticles" refers to graphite as microparticles, and "microparticles" refers to particles having an average particle size or diameter on the order of several nanometers to several micrometers (approximately several nanometers to several micrometers). Specifically, graphite microparticles are graphite with an average size less than or equal to about 2.5 μm. By including a coating layer containing graphite microparticles, even using a small amount of graphite microparticles, the positive electrode active material can possess electrical conductivity. The graphite microparticles can be commercially available graphite or graphite manufactured from it, provided that the graphite microparticles meet the aforementioned average particle size requirement.

[0088] There are no particular restrictions on the type of graphite microparticles, as long as they include graphite and can include, for example, natural or artificial graphite.

[0089] Graphite microparticles can be particles with a plate geometry, and the average size of the graphite microparticles can be less than or equal to about 2 μm, less than or equal to about 1.5 μm, less than or equal to about 1 μm, less than or equal to about 0.7 μm, less than or equal to about 0.5 μm, or less than or equal to about 0.3 μm and can be greater than or equal to about 0.01 μm, greater than or equal to about 0.05 μm, greater than or equal to about 0.07 μm, greater than or equal to about 0.1 μm, or greater than or equal to about 0.2 μm. The average size of the graphite microparticles can be measured by a particle size analyzer, and "average size of graphite microparticles" means the size of particles having a cumulative volume of 50% in the particle size distribution. Furthermore, particle size here can mean the length of the major axis in the plane perpendicular to the thickness direction in the plate geometry. When the average size of the graphite microparticles meets the above ranges, a coating layer of uniform thickness can be formed on the surface of the core particles, and the positive electrode active material including the coating layer can exhibit powder conductivity.

[0090] Graphite microparticles may have a diameter D of less than or equal to about 500 nm, for example, about 10 nm to about 500 nm, about 20 nm to about 400 nm, about 30 nm to about 300 nm, about 40 nm to about 200 nm, about 50 nm to about 150 nm, or about 60 nm to about 120 nm. 10 The diameter D of the graphite particles 10 The particle size distribution of graphite microparticles can be obtained by using a particle size analyzer, and the diameter D is taken as the diameter of the particles that have a cumulative volume of 10% in the particle size distribution. 10 Furthermore, grain size can refer to the length of the major axis in a plane perpendicular to the thickness direction within the plate geometry.

[0091] Graphite particles may have a diameter D of less than or equal to about 20 μm, for example, about 5 μm to about 20 μm, about 6 μm to about 18 μm, about 7 μm to about 16 μm, about 8 μm to about 14 μm, about 9 μm to about 12 μm, or about 10 μm to about 12 μm. 90 The diameter D of the aforementioned graphite particles 90 The particle size distribution of graphite microparticles can be obtained by using a particle size analyzer, and the diameter D is taken as the diameter of the particles that account for 90% of the cumulative volume in the particle size distribution. 90 Furthermore, grain size can refer to the length of the major axis in a plane perpendicular to the thickness direction within the plate geometry.

[0092] The span value of graphite particles can be greater than about 1, for example, about 1.05 to about 8, about 1.1 to about 7, about 1.2 to about 6, or about 1.4 to about 5. The span of graphite particles can be expressed as (D90 -D 10 ) / D 50 Calculate, and D 10 D 50 and D 90 These values ​​can be taken as diameters corresponding to 10%, 50%, and 90% of the cumulative volume in the particle size distribution, respectively. A larger span value for graphite particles means a wider particle size distribution, while a smaller span value means a narrower and more uniform particle size distribution.

[0093] Graphite particles can have a size of approximately 30 μm. 2 / g to approximately 400 m 2 / g, for example, about 50 m 2 / g to approximately 400 m 2 / g, approximately 100 m 2 / g to approximately 400 m 2 / g, approximately 150 m 2 / g to approximately 400 m 2 / g, approximately 200 m 2 / g to approximately 400 m 2 / g, approximately 250 m 2 / g to approximately 400m 2 / g or approximately 300 m 2 / g to approximately 400 m 2 / g BET specific surface area. The BET specific surface area of ​​graphite particles can be measured using the Brunauer-Emmett-Teller (BET) method. When the BET specific surface area of ​​graphite particles meets the above range, uniform coating is possible, and electrical conductivity can be achieved even with a small amount of coating.

[0094] Graphite microparticles may have a ratio of length of the long axis in the planar direction to thickness of approximately 50 to approximately 1000 in the plate geometry. When the ratio of the length of the long axis in the planar direction to thickness of the graphite microparticles meets the above range, a uniform coating layer can be formed, and the electrical conductivity of the positive electrode active material can be improved. The ratio of the length of the long axis in the planar direction to thickness of the graphite microparticles can be measured based on electron microscopy images of the graphite microparticles. In scanning electron microscopy images of graphite microparticles, the thickness of the graphite microparticles can be measured, and the length of the long axis in the planar direction orthogonal to the thickness direction can be measured to calculate the ratio. The thickness and long axis length of the graphite microparticles may mean the arithmetic mean of the values ​​obtained from image analysis of multiple graphite microparticles. In addition, the combination of the thickness and long axis length of the graphite microparticles is not limited to the values ​​measured from a single identical graphite microparticle, and may be a combination of values ​​measured from different graphite microparticles.

[0095] Graphite microparticles may have a Raman spectral density of about 0.15 to about 0.50, for example about 0.15 to about 0.45, about 0.18 to about 0.45, or about 0.20 to about 0.40 at 1350 cm⁻¹. -1 Nearby peak intensity I D At 1580 cm -1 Nearby peak intensity I G The ratio I D / I G When the I of graphite particles D / I G When the values ​​meet the above range, a coating layer with a uniform thickness can be formed on the surface of the core particles, and the positive electrode active material can maximize the adhesion and conductivity with the electrode plate.

[0096] Based on the total weight (100 wt%) of the positive electrode active material, graphite particles may be included in the coating layer in amounts from about 0.01 wt% to about 1 wt%, for example, from about 0.05 wt% to about 0.9 wt%, from about 0.1 wt% to about 0.8 wt%, from about 0.1 wt% to about 0.6 wt%, or from about 0.1 wt% to about 0.4 wt%. Even when the graphite particles meet the aforementioned range based on the total weight of the positive electrode active material, the powder conductivity of the positive electrode active material can be maintained, thereby achieving electrical conductivity. If the graphite particles are outside the aforementioned amount (wt%) range based on the total weight of the positive electrode active material, the energy density may decrease, degrading the performance of the battery.

[0097] The coating layer, including graphite microparticles, can be in the form of a film continuously surrounding the surface of the core particle or in the form of islands discontinuously existing on the surface of the core particle. The coating layer can be in the form of a film continuously surrounding the surface of the core particle or in the form of a shell surrounding the entire surface of the core particle. This is different from the form of islands discontinuously existing on the surface of the core particle. According to some embodiments, the coating layer can completely cover the surface of the core particle to have a very thin and uniform thickness, such that the positive electrode active material does not exhibit an increase in resistance or a decrease in capacity, and the positive electrode active material can exhibit improved structural stability, effectively suppressing side reactions with the electrolyte, and improving the electrical conductivity of the positive electrode active material (so that the amount of conductive material in the positive electrode can be reduced while relatively increasing the amount of positive electrode active material), thereby achieving high capacity and high energy density of the battery.

[0098] The coating layer can have a thickness of about 1 nm to about 40 nm, for example, about 1 nm to about 35 nm, about 1 nm to about 30 nm, about 1 nm to about 25 nm, or about 1 nm to about 20 nm. If the thickness of the coating layer is within these ranges, the coating layer can neither increase the resistance nor decrease the capacity; on the contrary, it can improve the structural stability of the positive electrode active material, effectively suppress side reactions with the electrolyte, and improve the electrical conductivity of the positive electrode active material. The thickness of the coating layer can be measured by, for example, TOF-SIMS, XPS, or EDS analysis, and the thickness range of the coating layer can be measured by TEM-EDS line profiling.

[0099] The coating layer can be thin, ranging from tens to hundreds of nanometers in thickness, but can be uniform in thickness. The deviation in coating layer thickness within a single positive electrode active material particle can be less than or equal to about 20%, less than or equal to about 18%, or less than or equal to about 15%. The deviation in coating layer thickness per particle refers to the thickness of the coating layer within a single positive electrode active material particle. The deviation in coating layer thickness can be calculated as follows: the thickness of approximately 10 points in an electron microscope image of a cross-section of a single positive electrode active material particle is measured to calculate the arithmetic mean; then the absolute value of the difference between a data point and the arithmetic mean is divided by the arithmetic mean and multiplied by 100. A coating layer thickness deviation or standard deviation within the above range indicates that a uniformly thick coating layer forms well as a film on the surface of the positive electrode active material particle, thereby improving the structural stability of the positive electrode active material, effectively suppressing side reactions with the electrolyte, minimizing the increase in resistance or decrease in capacity due to coating, and achieving good electrical conductivity for the positive electrode active material.

[0100] In some embodiments, the difference between the highest and lowest thicknesses of the coating layer may be less than or equal to about 17 nm, for example, less than or equal to about 15 nm, less than or equal to about 10 nm, or less than or equal to about 8 nm and greater than or equal to about 0.01 nm, greater than or equal to about 0.05 nm, greater than or equal to about 0.07 nm, or greater than or equal to about 0.1 nm. A difference between the highest and lowest thicknesses of the coating layer satisfying the above ranges means that a coating layer of uniform thickness is well formed as a film on the surface of the positive electrode active material particles, and therefore, the positive electrode active material can maximize adhesion to the electrode plate and maximize conductivity. The highest and lowest thicknesses of the coating layer can be measured based on electron microscopy images of the positive electrode active material. In an electron microscopy image of a cross-section of the positive electrode active material particles, the thickness of the thickest portion of the cross-section of the coating layer can be defined as the highest thickness of the coating layer, and the thickness of the thinnest portion can be defined as the lowest thickness of the coating layer. The thickness of the coating layer can be the vertical distance from the outer surface of the core particle to the outer surface of the coating layer. Scanning electron microscopes or transmission electron microscopes can be used as electron microscopes.

[0101] Methods for preparing positive electrode active materials

[0102] A method for preparing a positive electrode active material according to some embodiments includes: preparing core particles comprising a lithium transition metal composite compound; preparing graphite microparticles; and dry mixing the core particles and graphite microparticles to obtain the positive electrode active material. In this document, the graphite microparticles may have an average size of less than or equal to about 2.5 μm, and the positive electrode active material has a size greater than or equal to about 0.1 mS / cm when measured at a pressure of about 250 MPa. -1 The powder conductivity. One or more details of the resulting positive electrode active material may be the same as those of the positive electrode active materials described above, and therefore some of the above details will be repeated in the following description of the method for preparing the positive electrode active material.

[0103] In a method for preparing a positive electrode active material according to some embodiments, graphite, used as a conductive material, can be pulverized to prepare graphite microparticles, which are used to form a coating layer containing graphene and having a layered structure on the surface of the core particles. The positive electrode active material including the graphene-containing coating layer allows for uniform coating of the positive electrode active material and provides electrical conductivity. Furthermore, during the manufacture of the positive electrode, the amount of added conductive material can be minimized, thus relatively increasing the amount of added positive electrode active material, which can provide a rechargeable lithium battery with high capacity and high energy density including the positive electrode active material. On the other hand, if graphite microparticles are used as the coating material, dry coating can be employed, thereby reducing costs.

[0104] Core Particle Preparation

[0105] Core particles comprising lithium transition metal complexes can be prepared. The core particles prepared in this step are described in the same manner as those described above for positive electrode active materials and will not be repeated.

[0106] Preparation of graphite microparticles

[0107] Prepare graphite microparticles. Specific properties of the graphite microparticles prepared in this step (e.g., average size or Ig) are also important. D / I G This can be described in the same way as those of the above positive electrode active materials and will not be repeated.

[0108] In preparing graphite microparticles, the graphite microparticles (which may be the same as or similar to the graphite microparticles in the above-mentioned positive electrode active material) may be obtained from commercially available sources or may be prepared by crushing graphite to prepare graphite microparticles.

[0109] In some embodiments, the preparation of graphite microparticles may include crushing graphite to prepare graphite microparticles.

[0110] There are no particular restrictions on the type of graphite, and it can be, for example, flake graphite. The graphite can be the same type used in rechargeable lithium batteries.

[0111] Flake graphite can have an average size of about 3 μm to about 25 μm, for example, about 3 μm to about 20 μm, about 3 μm to about 15 μm, about 3 μm to about 10 μm, about 3 μm to about 8 μm, about 3 μm to about 6 μm, about 3 μm to about 4 μm, or about 3 μm to about 3.5 μm. The average size of flake graphite can be measured from scanning electron microscopy images. The average size of flake graphite can be measured by a particle size analyzer, and the average size of flake graphite means the size of particles having a cumulative volume of 50% in the particle size distribution. Furthermore, flake graphite can have a plate-like particle shape, and particle size here can mean the length of the major axis in the plane perpendicular to the thickness direction in the plate geometry.

[0112] Flake graphite may have a Raman spectroscopy intensity of greater than or equal to about 0.01 and less than about 0.15, for example, about 0.02 to about 0.14, about 0.08 to about 0.14, or about 0.1 to about 0.14 at 1350 cm⁻¹. -1 Nearby peak intensity I D At 1580 cm -1 Nearby peak intensity I G The ratio I D / I G .

[0113] Grinding processes can be used for pulverization. Grinding processes can utilize methods known to those skilled in the art, and can use apparatus such as ball mills, bead mills, spray mills, pin mills, roller mills, or air classifiers (ACMs).

[0114] A ball mill can be used for pulverization, and zirconia beads (ZrO2 beads) with a size of about 1 mm to about 3 mm can be used as the pulverizing medium. The size of the zirconia beads can be about 1.2 mm to about 2.8 mm, about 1.3 mm to about 2.7 mm, or about 1.5 mm to about 2.5 mm. If the size of the balls meets the above range, the particle size of the graphite particles can be controlled to the desired level.

[0115] When using a ball mill for pulverization, there is no particular limitation on the amount of balls to be introduced; however, for example, balls can be introduced in amounts ranging from about 500 parts by weight to about 2000 parts by weight per 100 parts by weight of graphite. Based on 100 parts by weight of graphite, balls can be added in amounts ranging from about 600 parts by weight to about 1800 parts by weight, about 700 parts by weight to about 1600 parts by weight, about 800 parts by weight to about 1400 parts by weight, or about 900 parts by weight to about 1100 parts by weight.

[0116] The grinding process can vary depending on the grinding apparatus and is not particularly limited. However, when using a ball mill, it can be carried out at speeds ranging from approximately 200 rpm to approximately 5000 rpm, for example, from approximately 250 rpm to approximately 4,500 rpm, from approximately 300 rpm to approximately 4,000 rpm, from approximately 400 rpm to approximately 3,000 rpm, or from approximately 600 rpm to approximately 3,000 rpm. The grinding time can vary depending on the grinding speed and is not particularly limited, but can be from approximately 30 minutes to approximately 3 hours or from approximately 35 minutes to approximately 3 hours. When the grinding speed and time meet the above ranges, the particle size of the graphite microparticles can be controlled to the desired level.

[0117] Graphite microparticles are prepared by pulverizing graphite according to the above-described pulverization method. These graphite microparticles possess excellent electrical conductivity, and simultaneously, by pulverizing graphite to produce graphite microparticles with a dense structure, the specific surface area of ​​the graphite microparticles can be increased.

[0118] Obtaining the active material for the positive electrode

[0119] Core particles and graphite microparticles are dry-mixed to obtain the positive electrode active material. In this step, crystalline carbon derived from graphite microparticles is coated onto the surface of the core particles according to the dry mixing process to form a coating layer containing graphene with a layered structure on the surface of the core particles. Even in the dry coating method, the coating layer formed on the surface of the core particles in this step is thin and uniform, which helps to reduce manufacturing costs. Furthermore, the amount of conductive material added during the manufacture of the positive electrode can be minimized, which increases the amount of positive electrode active material. Therefore, rechargeable lithium battery cells including the positive electrode active material can achieve high capacity and high energy density.

[0120] The core particles and graphite microparticles described in the following methods may be the same as or similar to the core particles and graphite microparticles described above, and therefore will not be repeated.

[0121] In the dry mixing process, graphite microparticles can be mixed in amounts ranging from about 0.1 parts by weight to about 0.5 parts by weight, for example, from about 0.1 parts by weight to about 0.4 parts by weight, from about 0.1 parts by weight to about 0.3 parts by weight, or from about 0.1 parts by weight to about 0.25 parts by weight, based on 100 parts by weight of core particles. Even when graphite microparticles are mixed within the above range based on 100 parts by weight of core particles, uniform coating can be achieved on the surface of the core particles, and electrical conductivity of the positive electrode active material can be achieved. Furthermore, since the amount of positive electrode active material can be increased by minimizing the amount of conductive material during the manufacture of the positive electrode, high capacity and high energy density can be achieved.

[0122] Dry mixing processes can include any method that forms a coating by applying mechanical energy to core particles comprising lithium transition metal complexes and graphite microparticles without the use of solvents. In this document, the term "dry mixing process" means a state without intentional contact with solvents such as process solvents, or a state in which solvents are not intentionally included.

[0123] Dry mixing includes a) forming a coating layer by contacting the coating material, such as graphite microparticles, with the surface of the core particle while simultaneously agglomerating the graphite microparticles, and b) a method by bonding the coating material particles to the surface of the core particle through the movement of grinding media or a rotor within a device, while simultaneously mechanically combining the coating material particles with each other on the core particle and providing stress accompanying the coating material particles, such that the coating layer (with coating material particles) on the core particle is melted or softened by heat generated by stress, thereby bonding the coating material particles to the surface of the core particle. However, the invention is not limited thereto and may include any dry method within the technical field of this disclosure that can achieve the same dry mixing objective.

[0124] Dry mixing can be performed using ball milling methods such as planetary ball milling, low-speed ball milling, high-speed ball milling, or mechanical fusion. For example, a dry method can be performed using mechanical fusion, which involves placing the mixture in a rotating container, fixing the mixture to the inner wall of the container by centrifugal force, and then compressing the mixture through a gap between the inner wall of the container and an arm head slightly close to the inner wall. Mechanical fusion corresponds to method b) above. The container can be, for example, a mixer with internal blades, and the mixer can have a diameter of about 5 cm to about 15 cm and a gap of about 0.1 mm to about 5 mm. Furthermore, there is no particular limitation on the speed of the mixer, but it can be, for example, about 1,000 rpm to about 5,000 rpm, about 1,500 rpm to about 4,500 rpm, about 2,000 rpm to about 4,000 rpm, or about 2,500 rpm to about 3,500 rpm, and the rotation time can vary depending on the speed, but can be about 30 seconds to about 1 hour, about 1 minute to about 30 minutes, or about 5 minutes to about 15 minutes.

[0125] By forming a coating layer containing graphite particles according to the above-described dry mixing process, no solvent is required (unlike when forming a coating layer according to existing wet methods), and therefore, manufacturing costs such as solvent purchase costs and solvent treatment costs after wet coating can be reduced.

[0126] Rechargeable lithium batteries

[0127] A rechargeable lithium battery according to some embodiments includes an electrolyte, a negative electrode, and a positive electrode. The positive electrode includes a positive electrode current collector and a layer of positive electrode active material on the positive electrode current collector, comprising the aforementioned positive electrode active material. A rechargeable lithium battery according to some embodiments may include a positive electrode with reduced powder resistance by including the aforementioned positive electrode active material. Furthermore, because the aforementioned positive electrode active material itself exhibits electrical conductivity, the same effect can be achieved even when using a relatively small amount of conductive material compared to when using known positive electrode active materials. Therefore, a relatively large amount of positive electrode active material can be included, and thus, the energy density of the rechargeable lithium battery can be improved.

[0128] A rechargeable lithium battery may include a positive electrode, a negative electrode, a separator between the positive and negative electrodes, and an electrolyte.

[0129] In some embodiments, the all-solid-state rechargeable battery includes a positive electrode, a negative electrode, and a solid electrolyte layer located between the positive and negative electrodes.

[0130] Depending on the geometry of the rechargeable lithium battery, rechargeable lithium batteries can be classified as cylindrical, prismatic, pouch-shaped, or coin-shaped. Figures 1 to 4Each of the above is a schematic diagram illustrating a rechargeable lithium battery according to some embodiments of the present disclosure. In particular, Figure 1 Displays a cylindrical battery. Figure 2 Displays a prismatic battery, and Figure 3 and 4 Each battery is shown with a pouch geometry. The rechargeable lithium battery 100 includes an electrode assembly 40 and a housing 50. The electrode assembly 40 has a separator 30 between a positive electrode 10 and a negative electrode 20, and the electrode assembly 40 is housed within the housing 50. The positive electrode 10, negative electrode 20, and separator 30 may be impregnated with an electrolyte (not shown). The rechargeable lithium battery 100 may include a seal 60 for sealing the housing 50, such as... Figure 1 As shown. Additionally, in Figure 2 In this context, the rechargeable lithium battery 100 may include a positive electrode lead connector 11, a positive electrode terminal 12, a negative electrode lead connector 21, and a negative electrode terminal 22. For example... Figure 3 and 4 As shown, the rechargeable lithium battery 100 includes electrode terminals 70, or more specifically, positive electrode terminals 71 and negative electrode terminals 72, which serve as electrical paths for leading current formed in the electrode assembly 40 to the outside.

[0131] positive electrode

[0132] The positive electrode includes a positive electrode current collector and a positive electrode active material layer disposed on the positive electrode current collector, the positive electrode active material layer including the aforementioned positive electrode active material.

[0133] There are no particular restrictions on the positive electrode current collector, as long as it is conductive and does not cause chemical changes in the rechargeable lithium battery, and it can be an aluminum foil or stainless steel foil with a thickness of about 10 μm to about 15 μm.

[0134] The positive electrode active material includes the aforementioned positive electrode active material. Specific details of the positive electrode active material are the same as described above and are therefore omitted below.

[0135] Based on the total weight (100 wt%) of the positive electrode active material layer, the amount of positive electrode active material can be approximately 60 wt% to approximately 99.9 wt%, approximately 70 wt% to approximately 99.8 wt%, approximately 80 wt% to approximately 99 wt%, or approximately 90 wt% to approximately 98 wt%. When the above-described positive electrode active material is included, the same effect can be achieved even when using a relatively small amount of conductive material compared to when using known positive electrode active materials. Therefore, a relatively large amount of positive electrode active material can be included, and thus, the energy density can be improved.

[0136] The positive electrode active material layer may optionally further include a binder, a conductive material, or a combination thereof.

[0137] Binders improve the adhesion properties between the particles of the positive electrode active material and with the positive electrode current collector. Examples of binders may include polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers (ethylene oxide-containing polymers), polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, (meth)acrylated styrene-butadiene rubber, epoxy resins, (meth)acrylate resins, polyester resins, and nylon, but binders are not limited to these.

[0138] Based on the total weight (100 wt%) of the positive electrode active material layer, the amount of binder in the positive electrode active material layer may be from about 0.1 wt% to about 5 wt%, and may be, for example, from about 0.1 wt% to about 3 wt%, from about 0.1 wt% to about 1 wt%, or from about 0.5 wt% to about 1 wt%.

[0139] Conductive materials are included to provide electrode conductivity, and any electrically conductive material may be used as a conductive material unless it causes a chemical change. Examples of conductive materials may include carbon-based materials such as natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fibers, carbon nanofibers and / or carbon nanotubes; metal-based materials including metal powders or metal fibers of copper, nickel, aluminum and / or silver; conductive polymers such as polyphenylene derivatives; or mixtures thereof.

[0140] In the positive electrode active material layer, conductive material may be included in very small amounts, or even not at all. By minimizing the amount of conductive material in the positive electrode active material layer, energy density can be increased, and mixing density (mixture density) can be improved.

[0141] Based on the total weight (100 wt%) of the positive electrode active material layer, the amount of conductive material in the positive electrode active material layer may be less than or equal to about 5 wt%, less than or equal to about 4 wt%, less than or equal to about 3 wt%, less than or equal to about 2 wt%, less than or equal to about 1 wt%, less than or equal to about 0.5 wt%, or about 0 wt%. The positive electrode active material layer may include the conductive positive electrode active material as described above, and the required amount of conductive material may be minimized or the need for conductive material may be completely eliminated, which may allow for an increased amount of positive electrode active material.

[0142] The density of the positive electrode active material layer can be from about 2.0 g / cc to about 6.0 g / cc, for example, from about 2.3 g / cc to about 5.8 g / cc, from about 2.5 g / cc to about 5.7 g / cc, or from about 2.5 g / cc to about 5.5 g / cc. Alternatively, when the lithium transition metal composite compound of the core particles is a lithium cobalt-based oxide, the density of the positive electrode active material layer can be from about 3.5 g / cc to about 5.0 g / cc, from about 3.7 g / cc to about 4.9 g / cc, from about 3.8 g / cc to about 4.8 g / cc, or from about 4.0 g / cc to about 4.5 g / cc. When the density of the positive electrode active material layer meets the above ranges, the energy density of the rechargeable lithium battery can be improved. Because the above-mentioned positive electrode active material has high particle strength and surface lubricity, compression processing can be performed under greater pressure. Furthermore, because the surface lubricity of the positive electrode active material is high, the compression efficiency of the positive electrode can be improved through a sliding effect. In addition, because the compression process can be carried out under greater pressure, the pores of the electrode plate in the positive electrode active material layer can be reduced, and the density of the positive electrode active material layer can be further improved.

[0143] Furthermore, the resistance of the positive electrode active material layer can be less than or equal to about 35 Ω·cm, less than or equal to about 30 Ω·cm, less than or equal to about 25 Ω·cm, or less than or equal to about 20 Ω·cm and can be greater than or equal to about 0.5 Ω·cm, greater than or equal to about 1.0 Ω·cm, greater than or equal to about 3.0 Ω·cm, greater than or equal to about 5.0 Ω·cm, or greater than or equal to about 5.5 Ω·cm. Because the positive electrode active material layer includes the above-mentioned positive electrode active material, even if the positive electrode active material layer does not include a separate conductive material or includes a very small amount of conductive material, the positive electrode active material layer can still exhibit excellent electronic conductivity and achieve low resistance.

[0144] The porosity of the positive electrode can be less than or equal to about 30%, less than or equal to about 25%, less than or equal to about 20% and greater than or equal to about 1%, greater than or equal to about 5%, or greater than or equal to about 7%. When the porosity of the positive electrode meets the above ranges, the capacity and energy density of the positive electrode can be improved. The porosity of the positive electrode refers to the ratio of the volume of pores present in the positive electrode to the total volume of the positive electrode, and can be measured, for example, by mercury porosimetry (mercury porosimetry).

[0145] In addition to the components described above, without hindering the purpose of the present invention, the positive electrode active material layer may further include positive electrode active materials other than those described above, irreversible positive electrode additives, or combinations thereof.

[0146] Irreversible positive electrode additives are compounds that act as sacrificial positive electrodes, compensating for the irreversible conversion of Li that no longer participates in the charging / discharging reaction by participating in the formation of an SEI (solid electrolyte interphase) film on the surface of the negative electrode during charging / discharging. Irreversible positive electrode additives are compounds that decompose during the formation process to provide Li and do not participate in subsequent charging / discharging processes. By adding such irreversible positive electrode additives, consumed lithium can be replenished, thereby compensating for lithium loss and improving the battery's energy density, cycle life, and stability.

[0147] Irreversible positive electrode additives include compounds used as sacrificial positive electrodes, such as Fe-containing oxides, Mn-containing oxides, and Co-containing oxides.

[0148] Fe-containing oxides may include Li5FeO4, LiFeO2, LiFe5O8, or combinations thereof. Mn-containing oxides may include overlithiated manganese oxides, and examples of which may include Li6MnO4. Co-containing oxides may include overlithiated cobalt oxides, and examples of which may include Li6CoO4. Fe-containing oxides have greater electrochemical properties than Mn-containing oxides, and therefore, Fe-containing oxides can play a full role in compensating for irreversible Li and improving the utilization rate of the positive electrode active material. Additionally, when using Co-containing oxides, Li6CoO4 decomposes during charging and discharging to form Li2O and CoO, and the formed CoO dissolves in the electrolyte solution to form Co. 2+ This causes Co to be eluted from the negative electrode, thus degrading the battery's performance.

[0149] negative electrode

[0150] The negative electrode for a rechargeable lithium battery includes a negative electrode current collector and a layer of negative electrode active material on the negative electrode current collector. The negative electrode active material layer includes a negative electrode active material and may optionally further include a binder, a conductive material, or a combination thereof.

[0151] Negative electrode active materials include materials capable of reversibly inserting / deintercalating lithium ions, lithium metal, lithium metal alloys, materials capable of doping and dedoping lithium, or transition metal oxides.

[0152] Materials capable of reversibly inserting / deintercalating lithium ions may include carbon-based negative electrode active materials, such as crystalline carbon, amorphous carbon, or combinations thereof. Crystalline carbon may be irregular, flake-like, spherical, or fibrous natural or artificial graphite. Amorphous carbon may be soft carbon, hard carbon, mesophase pitch carbonization products, or calcined coke.

[0153] As the alloy of lithium metal, an alloy of lithium and Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Si, Sb, Pb, In, Zn, Ba, Ra, Ge, Al, Sn, or a combination thereof may be used.

[0154] The material capable of doping and dedoping lithium may be a Si-based negative electrode active material or a Sn-based negative electrode active material. The Si-based negative electrode active material may be silicon, a silicon-carbon composite, SiO x (0<x≤2), a Si-Q alloy (wherein Q is an alkali metal, an alkaline earth metal, a Group 13 element, a Group 14 element [other than Si], a Group 15 element, a Group 16 element, a transition metal, a rare earth element, or a combination thereof, and for example Mg, Ca, Sr, Ba, Ra, Sc, Y, Ti, Zr, Hf, Rf, V, Nb, Ta, Db, Cr, Mo, W, Sg, Tc, Re, Bh, Fe, Pb, Ru, Os, Hs, Rh, Ir, Pd, Pt, Cu, Ag, Au, Zn, Cd, B, Al, Ga, Sn, In, Tl, Ge, P, As, Sb, Bi, S, Se, Te, Po, or a combination thereof), or a combination thereof. The Sn-based negative electrode active material may be Sn, SnO₂, a Sn alloy, or a combination thereof.

[0155] The silicon-carbon composite may be a composite of silicon and amorphous carbon. The average particle diameter D of the silicon-carbon composite particles 50 may be, for example, from about 0.5 μm to about 20 μm. According to some embodiments, the silicon-carbon composite may be in the form of silicon particles and amorphous carbon coated on surfaces of the silicon particles. The silicon-carbon composite may include secondary particles (core) in which silicon primary particles are aggregated and an amorphous carbon coating layer (shell) on surfaces of the secondary particles. Amorphous carbon may also be present between the silicon primary particles; in particular, the silicon primary particles may be coated with amorphous carbon. The secondary particles may be dispersed in an amorphous carbon matrix.

[0156] The silicon-carbon composite may further include crystalline carbon. The silicon-carbon composite may include: a core including crystalline carbon and silicon particles, and an amorphous carbon coating layer on a surface of the core. The crystalline carbon may be artificial graphite, natural graphite, or a combination thereof. The amorphous carbon may include soft carbon or hard carbon, a mesophase pitch carbonized product, or calcined coke.

[0157] When the silicon-carbon composite includes silicon and amorphous carbon, based on 100 wt% of the silicon-carbon composite, the amount of silicon may be from about 10 wt% to about 50 wt%, and the amount of amorphous carbon may be from about 50 wt% to about 90 wt%. In addition, when the composite includes silicon, amorphous carbon, and crystalline carbon, based on 100 wt% of the silicon-carbon composite, the amount of silicon may be from about 10 wt% to about 50 wt%, the amount of crystalline carbon may be from about 10 wt% to about 70 wt%, and the amount of amorphous carbon may be from about 20 wt% to about 40 wt%.

[0158] In addition, the thickness of the amorphous carbon coating layer may be about 5 nm to about 100 nm. The average particle diameter D of the silicon particles (primary particles) 50 may be about 10 nm to about 1 μm or about 10 nm to about 200 nm. The silicon particles may exist as elemental silicon, may exist in the form of a silicon alloy, or may exist in an oxidized form. The oxidized form of silicon may be represented by SiO x (0<x≤2). The Si:O atomic ratio representing the oxidation degree may be about 99:1 to about 33:67. As used herein, when no additional definition is provided, the average particle diameter D 50 refers to the diameter of the particle at a cumulative volume of about 50 volume% in the particle size distribution.

[0159] The Si-based negative electrode active material or Sn-based negative electrode active material may be mixed with a carbon-based negative electrode active material. When a mixture of the Si-based negative electrode active material or Sn-based negative electrode active material and the carbon-based negative electrode active material is used, the mixing ratio by weight may be about 1:99 to about 90:10.

[0160] Based on 100 wt% of the negative electrode active material layer, the negative electrode active material may be included in an amount of about 90 wt% to about 99.8 wt% or about 94 wt% to about 99 wt%.

[0161] The binder serves to adhere the negative electrode active material particles to each other, and also serves to adhere the negative electrode active material to the negative electrode current collector. The binder may be a non-aqueous binder, an aqueous binder, a dry binder, or a combination thereof.

[0162] The non-aqueous binder may include polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene-propylene copolymer, polystyrene, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polyamide-imide, polyimide, or a combination thereof.

[0163] The aqueous binder may include styrene-butadiene rubber, (meth)acrylated styrene-butadiene rubber, (meth)acrylonitrile-butadiene rubber, (meth)acrylic rubber, butyl rubber, fluororubber, polyethylene oxide, polyvinylpyrrolidone, polyepichlorohydrin, polyphosphazene, poly(meth)acrylonitrile, ethylene-propylene-diene copolymer, polyvinylpyridine, chlorosulfonated polyethylene, latex, polyester resin, (meth)acrylic resin, phenolic resin, epoxy resin, polyvinyl alcohol, or a combination thereof.

[0164] When an aqueous binder is used as the negative electrode binder, a cellulose-based compound capable of imparting viscosity may be further included. As the cellulose-based compound, one or more of carboxymethyl cellulose, hydroxypropyl methyl cellulose, methyl cellulose, or alkali metal salts thereof may be mixed and used. The alkali metal may be Na, K or Li.

[0165] Dry adhesives can be polymeric materials that can be turned into fibers and can be, for example, polytetrafluoroethylene, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polyethylene oxide, or combinations thereof.

[0166] Conductive materials are included to provide electrode conductivity, and any electrically conductive material can be used as a conductive material unless it causes a chemical change. Examples of conductive materials include carbon-based materials such as natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fibers, carbon nanofibers and / or carbon nanotubes; metal-based materials including metal powders or metal fibers of copper, nickel, aluminum and / or silver; conductive polymers such as polyphenylene derivatives; or mixtures thereof.

[0167] Based on 100% by weight of the negative electrode active material layer, the amount of binder may be from about 0.1% by weight to about 5% by weight, and based on 100% by weight of the negative electrode active material layer, the amount of conductive material may be from about 0.1% by weight to about 5% by weight.

[0168] There are no particular restrictions on the negative electrode current collector, as long as it is conductive and does not cause chemical changes in the rechargeable lithium battery, and it can be a copper foil with a thickness of about 10 μm to about 15 μm.

[0169] electrolytes

[0170] The electrolyte used in rechargeable lithium batteries may be an electrolyte solution, which may include non-aqueous organic solvents and lithium salts.

[0171] Non-aqueous organic solvents are used as media for transporting ions that participate in the electrochemical reactions of a battery. Non-aqueous organic solvents can be carbonate (carbonate-based) solvents, ester (ester-based) solvents, ether (ether-based) solvents, ketone (ketone-based) solvents, alcohol (alcohol-based) solvents, aprotic solvents, or combinations thereof.

[0172] Carbonate solvents may include dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), methyl ethyl carbonate (MEC), ethylene carbonate (EC), propylene carbonate (PC), and / or butyl carbonate (BC). Ester solvents may include methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, decanolactone, mevalonolactone, valproic acid lactone, and / or caprolactone. Ether solvents may include dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, dimethoxyethane, 2-methyltetrahydrofuran, 2,5-dimethyltetrahydrofuran, and / or tetrahydrofuran. Additionally, ketone solvents may include cyclohexanone, for example. Alcohol solvents may include ethanol or isopropanol, and aprotic solvents may include nitriles such as R-CN (where R is a C2 to C20 straight-chain, branched or cyclic hydrocarbon group, and may include double bonds, aromatic rings or ether groups); amides such as dimethylformamide; dioxolane such as 1,3-dioxolane or 1,4-dioxolane; and / or sulfolane.

[0173] Non-aqueous organic solvents can be used alone or in mixtures of two or more types, and when two or more types are used in mixtures, the mixing ratio can be appropriately adjusted according to the desired battery performance, as is widely known to those skilled in the art.

[0174] When using carbonate solvents, cyclic carbonates and chain carbonates can be mixed and used, and the cyclic carbonates and chain carbonates can be mixed in a volume ratio of about 1:1 to about 1:9.

[0175] Non-aqueous organic solvents may further include aromatic hydrocarbon organic solvents. Carbonate solvents and aromatic hydrocarbon organic solvents may be mixed and used in a volume ratio of about 1:1 to about 30:1.

[0176] The electrolyte solution may further include vinylene carbonate, vinylene carbonate, or ethylene carbonate compounds to improve the cycle life of the battery.

[0177] Examples of ethylene carbonate compounds may include fluoroethylene carbonate, difluoroethylene carbonate, chloroethylene carbonate, dichloroethylene carbonate, bromoethylene carbonate, dibromoethylene carbonate, nitroethylene carbonate, and cyanoethylene carbonate.

[0178] Lithium salts dissolved in non-aqueous organic solvents supply lithium ions in the battery, enabling basic operation of rechargeable lithium batteries and improving lithium ion transport between the positive and negative electrodes. Examples of lithium salts include LiPF6, LiBF4, LiSbF6, LiAsF6, LiClO4, LiAlO2, LiAlCl4, LiPO2F2, LiCl, LiI, LiN(SO2C2F5)2, Li(FSO2)2N (lithium bis(fluorosulfonyl)imide; LiFSI), LiC4F9SO3, LiN(C x F 2x+1 SO2)(C y F 2y+1 SO2 (where x and y are integers from 1 to 20), lithium trifluoromethanesulfonate, lithium tetrafluoroethanesulfonate, lithium difluorobis(oxalate)phosphate (LiDFBOP), lithium bis(oxalate)borate (LiBOB), or combinations thereof.

[0179] The concentration of lithium salt can be in the range of about 0.1 M to about 2.0 M. When the concentration of lithium salt is within the above range, the electrolyte solution has suitable ionic conductivity and viscosity, and therefore, excellent performance can be achieved, and lithium ions can move efficiently.

[0180] diaphragm

[0181] Depending on the type of rechargeable lithium battery, a separator may be present between the positive and negative electrodes. The separator may include multilayer membranes of polyethylene, polypropylene, polyvinylidene fluoride, or two or more layers thereof, and hybrid multilayer membranes such as polyethylene / polypropylene two-layer membranes, polyethylene / polypropylene / polyethylene three-layer membranes, and / or polypropylene / polyethylene / polypropylene three-layer membranes.

[0182] The diaphragm may include a porous substrate and a coating on one or both surfaces of the porous substrate, comprising organic materials, inorganic materials, or combinations thereof.

[0183] The porous substrate may be a polymer film formed from any of the following polymers: polyolefins such as polyethylene and polypropylene; polyesters such as polyethylene terephthalate and polybutylene terephthalate; polyacetal; polyamide; polyimide; polycarbonate; polyetherketone; polyaryletherketone; polyetherimide; polyamideimide; polybenzimidazole; polyethersulfone; polyphenylene ether; cyclic olefin copolymer; polyphenylene sulfide; polyethylene naphthalate; and polytetrafluoroethylene (e.g., Teflon). ® (TEFLON ® Polymers or copolymers or mixtures thereof. The porous substrate may be formed of glass fibers, or may be a membrane in which polymers and glass fibers are mixed.

[0184] The porous substrate may have a thickness of about 1 μm to about 40 μm, for example, about 1 μm to about 30 μm, about 1 μm to about 20 μm, about 5 μm to about 15 μm, or about 10 μm to about 15 μm.

[0185] Organic materials may include (meth)acrylic acid copolymers, which include a first structural unit and a second structural unit derived from (meth)acrylamide, the second structural unit including at least one structural unit derived from (meth)acrylic acid or (meth)acrylate and a structural unit derived from (meth)acryloylaminosulfonic acid or a salt thereof.

[0186] Inorganic materials may include Al₂O₃, SiO₂, TiO₂, SnO₂, CeO₂, MgO, NiO, CaO, GaO, ZnO, ZrO₂, Y₂O₃, SrTiO₃, BaTiO₃, Mg(OH)₂, boehmite, or combinations thereof, but are not limited to these. Inorganic materials may be in the form of particles (e.g., inorganic particles). The average particle size D of the inorganic particles... 50 It can be about 1 nm to about 2000 nm, for example about 100 nm to about 1000 nm or about 100 nm to about 700 nm.

[0187] Organic and inorganic materials can be mixed in a coating, or coatings containing organic materials and coatings containing inorganic materials can be stacked.

[0188] The coating thickness can be from about 0.5 μm to about 20 μm, for example from about 1 μm to about 10 μm or from about 1 μm to about 5 μm.

[0189] The invention is described in detail below by way of some exemplary embodiments. However, the embodiments described below only illustrate some embodiments of the invention, and the invention is not limited to the embodiments described below.

[0190] Examples 1 to 3

[0191] (1) Preparation of positive electrode active material

[0192] (a) Preparation of core particles

[0193] Core particles were prepared using lithium cobalt oxide (product name: 4.5V LiCoO2, manufacturer: XTC). Specifically, the 4.5V LiCoO2 consisted of a mixture with an average particle size D of 17 μm, prepared at a weight ratio of 7:3 ([large particle LCO]:[small particle LCO]). 50 Large-particle lithium cobalt oxide (LCO, LiCoO2) in single-particle form and with an average particle size D of 5 μm 50Small particles of lithium cobalt oxide (LCO, LiCoO2) in single-particle form.

[0194] (b) Preparation of graphite microparticles

[0195] 4 g of flake graphite (product name: G5, manufacturer: C-one; with an average size of 3 μm and a [Raman spectrum at 1350 cm⁻¹]) was used. -1 Nearby peak intensity I D At 1580 cm -1 Nearby peak intensity I G The ratio of ] I D / I G The graphite was mixed with 40 g of ZrO2 beads with a particle size of 2 mm. Subsequently, the flake graphite was milled at 1,000 rpm for 1 hour to prepare graphite microparticles.

[0196] Here, the graphite particles have an average size of 0.26 μm and a thickness of 300 μm. 2 The BET specific surface area of ​​ / g and 0.28 in the Raman spectrum at 1350 cm⁻¹ -1 Nearby peak intensity I D At 1580 cm -1 Nearby peak intensity I G The ratio I D / I G .

[0197] (c) Obtaining the positive electrode active material

[0198] Core particles and graphite microparticles (used as coating materials, with the weight ratio shown in Table 1) were placed in a dry mixer with a diameter of 9 cm and a gap of 2 mm. Then, a shear force of 3000 rpm was applied to the core particles and graphite microparticles for 10 minutes to obtain a positive electrode active material comprising core particles and a coating layer formed on the surface of the core particles and including graphene with a layered structure.

[0199] (2) Manufacturing of the positive electrode

[0200] A positive electrode active material was mixed with a binder mixture of polyvinylidene fluoride (PVdF) and polyacrylonitrile (PAN) at a weight ratio of 88.9:11.1 at a weight ratio of 99.1:0.9 (i.e., [positive electrode active material]:[binder]), and then dispersed in N-methylpyrrolidone as a solvent to prepare a positive electrode active material slurry. The positive electrode active material slurry was coated onto an aluminum film and dried to form a positive electrode active material layer, which was then compressed to manufacture the positive electrode. In the positive electrode, the positive electrode active material layer has a concentration of 16.5 mg / cm³. 2The loading level and mixing density were approximately 4.2 g / cc. Furthermore, SEM analysis of the compressed positive electrode confirmed that the active material layer of the positive electrode had a thickness of approximately 39 μm.

[0201] (3) Manufacturing of rechargeable lithium battery cells

[0202] The fabricated positive electrode was used in conjunction with a lithium metal counter electrode as the negative electrode to fabricate a 2032-type coin cell. An electrode assembly was formed by placing a membrane, made of porous polyethylene film and having a thickness of approximately 16 μm, between the positive electrode and the lithium metal counter electrode, and an electrolyte solution was injected into the electrode assembly. The electrolyte solution was prepared by mixing ethylene carbonate (EC) and ethyl methyl carbonate (EMC) at a volume ratio of 3:5 and dissolving 1.1 M LiPF6 in the mixed solvent.

[0203] Table 1:

[0204]

[0205] Comparative Example 1

[0206] Bimodal lithium cobalt oxide (LCO), which was used as the core particle in section (1) Preparation of positive electrode active material in Example 1, was used as the positive electrode active material. The positive electrode and rechargeable lithium battery cell were manufactured using the positive electrode active material in substantially the same manner as in Example 1.

[0207] Comparative Example 2

[0208] The positive electrode and rechargeable lithium battery cell were manufactured in essentially the same manner as in Example 2, except that the core particles and graphite microparticles were not dry-mixed, but rather mixed in a vial at 3,300 rpm for 1 minute using a vortex mixer, in comparison to the preparation in section "(1) Preparation of Positive Electrode Active Material" of Example 2. The positive electrode active material of Comparative Example 2 did not have a graphite microparticle coating layer on the surface of the core particles, like the positive electrode active material of Comparative Example 1.

[0209] Comparative Example 3

[0210] The positive electrode active material, positive electrode, and rechargeable lithium battery cell were manufactured in essentially the same manner as in Example 2, except that: instead of using graphite microparticles as the coating material to form a coating layer comprising graphene with a layered structure, a coating layer was formed by using reduced graphene oxide (rGO; product name: rGO-SF, manufacturer: JMC Fine Chem) having an average lateral dimension of 3 μm. The average lateral dimension of rGO was obtained by measuring the dimensions of rGO pieces in the horizontal direction (planar direction) and then averaging them.

[0211] Comparative Example 4

[0212] The positive electrode active material, the positive electrode, and the rechargeable lithium battery cell were manufactured in essentially the same manner as in Example 2, except that: instead of forming a coating layer by using Super P (product name: SUP-C65, manufacturer: TIMCAL) as in part “(1) Preparation of positive electrode active material” of Example 2, a coating layer including graphene with a layered structure was formed by using graphite microparticles as the coating material.

[0213] Comparative Example 5

[0214] The positive electrode active material, positive electrode, and rechargeable lithium battery cell were manufactured in essentially the same manner as in Example 2, except that: flake graphite (product name: G5, manufacturer: C-one; with an average size of 3 μm and a Raman spectroscopy of 0.12 at 1350 cm⁻¹) was used before pulverization. -1 Nearby peak intensity I D At 1580 cm -1 Nearby peak intensity I G The ratio of ] I D / I G Instead of preparing graphite microparticles by crushing graphite as in part “(1) Preparation of positive electrode active material” of Example 2, a coating layer is formed.

[0215] Evaluation Example 1: Electron Microscope Image Analysis

[0216] Figures 5 to 7 These are scanning electron microscope (SEM) images showing the surfaces of the positive electrode active materials in Examples 2, 1, and 5, respectively, according to some embodiments of the present disclosure.

[0217] It was confirmed that, unlike the positive electrode active material of Comparative Example 1, the positive electrode active material of Example 2 has a coating layer on the surface of the core particles. On the other hand, in Comparative Example 5, the coating layer was formed using flake graphite instead of graphite microparticles prepared by pulverizing flake graphite as in Example 2. As a result, no coating layer of graphene with a layered structure was formed on the surface of the core particles; instead, only a coating layer of flake graphite was present. These results indicate that forming a coating layer of graphene with a layered structure requires the use of graphite microparticles prepared by pulverizing flake graphite, as in Example 2.

[0218] Figure 8 and 9 These are transmission electron microscope (TEM) images showing the coating layer on a cross section of the positive electrode active material according to Examples 1 and 2, respectively, according to some embodiments of the present disclosure.

[0219] It is confirmed that the positive electrode active materials of Examples 1 and 2 each have a coating layer with a very thin and uniform thickness on the surface of the core particle, and the coating layer continuously wraps around the surface of the core particle.

[0220] Evaluation Example 2: Coating Layer Analysis of Positive Electrode Active Material

[0221] The number and thickness of the coating layers of the positive electrode active materials in Examples 1 to 3 were analyzed, and the results are shown in Table 2. In the positive electrode active materials of Comparative Examples 1 and 2, no evaluation was conducted because neither a coating layer nor a coating layer was formed. In the positive electrode active materials of Comparative Examples 3 to 5, no evaluation was conducted either, because although a coating layer was present, it was not formed from graphite particles.

[0222] Specifically, a scanning electron microscope was used to capture images of the cross-section of the positive electrode active material particles to measure the thickness and number of layers at 20 points in the image, and the values ​​of the thickness and number of layers across the 20 points were averaged.

[0223] Table 2:

[0224]

[0225] Evaluation Example 3: Measurement of powder resistance and powder conductivity of positive electrode active material

[0226] The powder conductivity of the positive electrode active materials of Examples 1 to 3 and Comparative Examples 3 to 5 was measured. In the positive electrode active materials of Comparative Examples 1 and 2, since neither a coating layer nor a coating layer was formed, no evaluation was performed.

[0227] The powder conductivity of the positive electrode active material was obtained as follows: the powder resistance of 3g of the positive electrode active material was measured by using a powder resistance meter equipped with a 4-pin probe (i.e., PD-600, Nittoseiko Analytech) while adjusting the pressure, and the reciprocal of the powder resistance value at a pressure of about 250 MPa was taken. The results are shown in Table 3 below.

[0228] To examine the powder resistance results based on the coating amount, the powder resistance to pressure of the positive electrode active materials in Examples 1 to 3 was measured, and the results are shown in... Figure 10 middle.

[0229] Figure 10 This is a graph showing the powder resistance versus pressure of the positive electrode active material prepared in Examples 1 to 3 according to some embodiments of the present disclosure.

[0230] It has been confirmed that the positive electrode active material coated with graphene having a layered structure exhibits a decrease in powder resistance with increasing pressure, which means that the powder resistance decreases significantly with increasing amount of graphene, thus confirming that the powder conductivity is significantly excellent.

[0231] Table 3:

[0232]

[0233] Referring to Table 3, Examples 1 to 3 (wherein graphene having a layered structure is coated by using graphite microparticles) exhibited powder conductivity even with a small amount of graphite microparticles added (i.e., from about 0.1% to about 0.4% by weight), but Comparative Examples 3 to 5 (wherein rGO, Super P, and graphite are coated, respectively) did not exhibit powder conductivity. The positive electrode active materials of Comparative Examples 3 to 5 were not expected to exhibit powder conductivity, even when the same approximately 0.2% by weight of rGO, Super P, and graphite included in the positive electrode active material of Example 2 was added. Therefore, it is confirmed that the positive electrode active materials according to some embodiments (wherein graphene having a layered structure is coated by using graphite microparticles) exhibit powder conductivity even when coated in smaller amounts than when coated with other coating materials.

[0234] Evaluation Example 4: Performance Evaluation of Rechargeable Lithium-ion Battery Cells

[0235] (1) Initial charge / discharge capacity and efficiency

[0236] The rechargeable lithium-ion battery cells of Examples 1 to 3 and Comparative Examples 1 to 5 were charged at 25°C with a constant current at a rate of 0.35 C to an upper limit voltage of 4.56 V and discharged at a rate of 0.35 C to a discharge cutoff voltage of 3 V to measure the initial charge / discharge capacity, which is shown in Table 4 below.

[0237] (2) Energy density

[0238] The energy density of rechargeable lithium-ion battery cells of Examples 1 to 3 and Comparative Examples 1 to 5 was measured as follows. Positive electrodes manufactured using the positive electrode active materials of Examples 1 to 3 and Comparative Examples 1 to 5 were compressed under the same conditions as described above to measure the thickness of each positive electrode. The electrode density and capacity were then calculated using the thicknesses, and the results are shown in Table 4 below.

[0239] Table 4:

[0240]

[0241] Referring to Table 4, compared with the rechargeable lithium-ion battery cells of Comparative Examples 1 to 5, it was confirmed that the rechargeable lithium-ion battery cells comprising the positive electrode active materials of Examples 1 to 3, which respectively use graphene with a layered structure coated with graphite microparticles, exhibited excellent efficiency of 90% or greater, significantly high energy density, and excellent initial charge / discharge capacity. This is because the positive electrode active material powders of Examples 1 to 3 are made conductive by using graphite microparticles to coat the graphene with a layered structure.

[0242] On the other hand, the rechargeable lithium battery cells of Comparative Examples 3 to 5 (in which a known carbon-based material is coated instead of graphene with a layered structure coated by using graphite microparticles) did not exhibit powder conductivity and thus exhibited degraded battery performance.

[0243] It has been confirmed that the positive electrode active material (in which graphene with a layered structure is coated on the surface of the core particle by using graphite microparticles) can exhibit its own powder conductivity, which makes it possible to use no conductive material, or at least to minimize the amount of conductive material, while using the maximum amount of positive electrode active material, thereby improving the overall battery performance.

[0244] While some embodiments have been described above, this disclosure is not limited to the embodiments described above. Rather, this disclosure is also intended to cover various modifications and equivalent arrangements of the embodiments described above.

[0245] <Description of representative figure labels>

[0246] 100: Rechargeable lithium battery; 10: Positive electrode

[0247] 11: Positive electrode lead connector 12: Positive electrode terminal

[0248] 20: Negative electrode 21: Negative electrode lead connector

[0249] 22: Negative electrode terminal; 30: Diaphragm

[0250] 40: Electrode assembly; 50: Housing

[0251] 60: Seal 70: Electrode terminal

[0252] 71: Positive electrode connector; 72: Negative electrode connector

Claims

1. Positive electrode active material, including: Including core particles of lithium transition metal complex compounds; and A coating layer of graphene with a layered structure is disposed on the surface of the core particle. When measured at a pressure of 250 MPa, the positive electrode active material exhibits a strength greater than or equal to 0.1 mS / cm. -1 The electrical conductivity of the powder.

2. The positive electrode active material according to claim 1, wherein the lithium transition metal composite compound comprises a lithium cobalt-based oxide represented by: Li a2 Co x2 M 3 y2 O 2-b2 X b2 , Where 0.9 ≤ a² ≤ 1.8, 0.7 ≤ x² ≤ 1, 0 ≤ y² ≤ 0.3, 0.9 ≤ x² + y² ≤ 1.1, and 0 ≤ b² ≤ 0.1, Where M 3 It is Al, B, Ba, Ca, Ce, Cr, Cu, Fe, Mg, Mn, Mo, Ni, Se, Si, Sn, Sr, Ti, V, W, Y, Zn, Zr or combinations thereof, and Where X is F, P, S or a combination thereof.

3. The positive electrode active material according to claim 1, wherein the core particle is in the form of a single particle.

4. The positive electrode active material according to claim 1, wherein the core particles comprise: Having an average particle size D greater than or equal to 0.1 μm and less than 9 μm 50 Small particles; and With an average particle size D of 9 μm to 30 μm 50 Large particles.

5. The positive electrode active material according to claim 1, wherein the coating layer comprises graphene having 2 to 50 layers.

6. The positive electrode active material according to claim 1, wherein the interlayer spacing d of the layered structure is... 002 The range is from 0.320 nm to 0.350 nm.

7. The positive electrode active material according to claim 1, wherein the graphene has a Raman spectroscopy intensity of 0.15 to 0.50 at 1350 cm⁻¹. -1 Nearby peak intensity I D At 1580 cm -1 Nearby peak intensity I G The ratio I D / I G .

8. The positive electrode active material according to claim 1, wherein the graphene in the coating layer is derived from graphite particles having an average size of less than or equal to 2.5 μm.

9. The positive electrode active material according to claim 1, wherein the amount of graphene is from 0.01% to 1% by weight based on 100% by weight of the positive electrode active material.

10. The positive electrode active material according to claim 1, wherein the coating layer is a film continuously surrounding the surface of the core particle, and The thickness of the coating layer is 1 nm to 40 nm.

11. A method for preparing the positive electrode active material according to any one of claims 1 to 10, the method comprising: Prepare core particles comprising lithium transition metal complex compounds; Prepare an average size D with a diameter less than or equal to 2.5 μm. 50 Graphite microparticles; as well as The core particles and the graphite microparticles are dry-mixed to obtain the positive electrode active material.

12. The method of claim 11, wherein the preparation of the graphite particles comprises pulverizing them to have an average size D of 3 μm to 25 μm. 50 Flake graphite.

13. The method of claim 12, wherein the pulverization is performed using a ball mill apparatus comprising zirconium oxide beads, each having a size of 1 mm to 3 mm, and Perform for a period of 30 minutes to 4 hours at speeds ranging from 200 rpm to 5,000 rpm.

14. The method of claim 11, wherein the dry mixing is performed in an amount ranging from 0.1 to 0.5 parts by weight of graphite microparticles per 100 parts by weight of the core particles.

15. A rechargeable lithium battery, including: Positive electrode; negative electrode; and Electrolytes, The positive electrode includes: Positive electrode current collector; and A positive electrode active material layer disposed on the positive electrode current collector, the positive electrode active material layer comprising the positive electrode active material according to any one of claims 1 to 10.